PENERAPAN SAK-ETAP PADA ENTITAS KOPERASI (Studi Kasus Pada KUD Tri Karsa Jaya Kec. Bangsalsari Kab. Jember) - Yulinartati, Yulinartati (Universitas Jember, 2013)
Financial reportis a report that shows the financial position consisting of revenues, expenses, assets, capital, and debt in a given period as a result of the transactions. Th financial statements should reflect the purpose cooperative of cooperatives, the balance of the calculation must be clearly informed cooperative activities with its members, because it is the income of members is presented separately f rom income derived from non - member transactions. Presentation was more reflective of that cooperative effort is more concerned with the transaction or service to the members of the non -members. Financial statements are the KUD